Hak Menolak dan Mematuhi Hukum dalam Kehidupan Masyarakat - Muhtadin, Muhtadin (AHKAM, 2022)
Law is a set of regulations and rules of norms which is made by the state and judicially enforceable. The rule of law ideally provides both justice and order to individual as well as social stability. This article is aimed to highlight some particular circumstances on how people tend to justify obedience or disobedience in society and of the nation. This article is written and analyzed by using normative legal research methods. A strong legal system should consist of legal rights and obligations as two inseparable parts. It also discusses about two aspects of legal relationships, namely: (a) power or authority of rights, (b) legal obligations. Practically, law has given legal consequences in people's lives in terms of right and obligation so that people will act obediently and appropriately by following the legal norms. The right to obey and disobey a law is inherent in people as legal subjects. This circumstances will give both benefits and consequences as defined on the purpose of the law itself.